Low‐dose total‐body carbon‐ion irradiations induce early transcriptional alteration without late Alzheimer's disease‐like pathogenesis and memory impairment in mice. Issue 7 (14th February 2014) - Wang, Bing; Tanaka, Kaoru; Ji, Bin; Ono, Maiko; Fang, Yaqun; Ninomiya, Yasuharu; Maruyama, Kouichi; Izumi‐Nakajima, Nakako; Begum, Nasrin; Higuchi, Makoto; Fujimori, Akira; Uehara, Yoshihiko; et al.
<x xml:space="preserve">Abstract</x> The cause and risk factors of Alzheimer's disease (AD) are largely unknown. Studies on possible radiation‐induced AD‐like pathogenesis and behavioral consequences are important because humans are exposed to ionizing radiation (IR) from various sources. It was reported that total‐body irradiations (TBI) at 10 cGy of low linear energy transfer (LET) X‐rays to mice triggered acute transcriptional alterations in genes associated with cognitive dysfunctions. However, it was unknown whether low doses of IR could induce AD‐like changes late after exposure. We reported previously that 10 cGy X‐rays induced early transcriptional response of several AD‐related genes in hippocampi without late AD‐like pathogenesis and memory impairment in mice. Here, further studies on two low doses (5 or 10 cGy) of high LET carbon‐ion irradiations are reported. On expression of 84 AD‐related genes in hippocampi, at 4 hr after TBI, 5 cGy induced a significant upregulation of three genes (Abca1, Casp3, and Chat) and 10 cGy led to a marked upregulation of one gene (Chat) and a downregulation of three genes (Apoe, Ctsd, and Il1α), and, at 1 year after TBI, one gene (Il1α) was significantly downregulated in 10 cGy‐irradiated animals. Changes in spatial learning ability and memory and induction of AD‐like pathogenesis were not detected by in vivo brain imaging for amyloid‐β peptide accumulation and by immunohistochemical staining of amyloid precursor protein, amyloid‐β protein, tau, and phosphorylated tau protein. These findings indicate that low doses of carbon‐ion irradiations did not cause behavioral impairment or AD‐like pathological change in mice. © 2014 Wiley Periodicals, Inc.